AU-Rich Long 3′ Untranslated Region Regulates Gene Expression in Bacteria - Zhao, Ju-Ping; Zhu, Hui; Guo, Xiao-Peng; Sun, Yi-Cheng (Frontiers in Microbiology, 2018)
3′ untranslated regions (3′ UTRs) and particularly long 3′ UTRs have been shown to act as a new class of post-transcriptional regulatory element. We previously reported that hmsT mRNA stability is negatively regulated by the 3′ UTR of hmsT in Yersinia pestis. To investigate more general effects of 3′ UTRs in Y. pestis, we selected 15 genes potentially possessing long 3′ UTRs with different AU content and constructed their 3′ UTR deletion mutants. Deletion of AU-rich 3′ UTRs increased mRNA levels, whereas deletion of 3′ UTRs with normal AU content resulted in slight or no changes in the mRNA level. In addition, we found that PNPase was important for 3′ UTR-mediated mRNA decay when the transcriptional terminator was Rho-dependent. Finally, we showed that ribosomes promote mRNA stability when bound to a 3′ UTR. Our findings suggest that functional 3′ UTRs might be broadly distributed in bacteria and their novel regulatory mechanisms require further investigation.